2019
DOI: 10.1111/beer.12262
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐national assessment of the effects of income level, socialization process, and social conditions on employees’ ethics

Abstract: Employees often experience ethical dilemmas throughout their service in an organization. This study utilized a multilevel standpoint to address employees’ differences in ethical reasoning. Hierarchical linear modeling was used to analyze responses from 40,485 full‐time employees across 54 countries. Drawing from Durkheim's concepts of the homo duplex, socialization process, and social conditions, this study found a positive relationship between employees’ income level and unethical reasoning. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 122 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…The NBS theory theorizes that national education systems and citizens' educational levels may affect CSR practices (Chapple & Moon, 2005; Matten & Moon, 2008). Tuliao, Chen, and Yeh (2020) found that employees' ethicality differed considerably across countries. In the context of the global refugee crisis, research has shown that refugees pose little challenge to skilled workers because most refugees seek career opportunities with low levels of skills (Scheve & Slaughter, 2001).…”
Section: Institutional Influence and Nbs Theorymentioning
confidence: 99%
“…The NBS theory theorizes that national education systems and citizens' educational levels may affect CSR practices (Chapple & Moon, 2005; Matten & Moon, 2008). Tuliao, Chen, and Yeh (2020) found that employees' ethicality differed considerably across countries. In the context of the global refugee crisis, research has shown that refugees pose little challenge to skilled workers because most refugees seek career opportunities with low levels of skills (Scheve & Slaughter, 2001).…”
Section: Institutional Influence and Nbs Theorymentioning
confidence: 99%